Advantage of Larger Interlayer Spacing of a Mo2Ti2C3 MXene Free-Standing Film Electrode toward an Excellent Performance Supercapacitor in a Binary Ionic Liquid–Organic Electrolyte - Gandla, Dayakar; Zhang, Fuming; Tan, Daniel Q (ACS omega, 2022)
MXenes show outstanding specific capacitance in aqueous electrolytes. However, the narrow potential window of aqueous electrolytes restrains the energy density. Ionic liquid electrolytes can provide a higher potential window and superior specific energy but are subject to slow ion transport and difficult intercalation for their larger ion size. It is desirable to explore larger interlayer-spaced (d-spaced) MXenes that can facilitate the large ion intercalation–deintercalation process. This work reports the first-ever supercapacitor application of the Mo2Ti2C3 MXene free-standing film electrode (f-Mo2Ti2C3) using 1 M 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)-imide (EMIMTFSI) in acetonitrile electrolyte. Without any preintercalating agents, the authors achieved an interlayer spacing of ∼2.4 nm in the f-Mo2Ti2C3 material through etching, followed by a vacuum-assisted filtration technique. The microstructure, electrochemical properties, and charge storage kinetics of the f-Mo2Ti2C3 outperform the conventional f-Ti3C2T x . The f-Mo2Ti2C3-based symmetric two-electrode device exhibited remarkable specific energy and specific power of 188 Wh kg–1 and 22 kW kg–1, respectively, along with a high specific capacitance of 152 F g–1. This larger d-spaced f-Mo2Ti2C3 can emerge as a better alternative to the conventional f-Ti3C2T x in ionic liquid electrolytes to design next-generation high-performance MXene supercapacitors.